CD4 depletion in HIV-infected haemophilia patients is associated with rapid clearance of immune complex-coated CD4+ lymphocytes - Daniel, Volker; Melk, Anette; Süsal, Caner; Weimer, Rolf; Zimmermann, R.; Huth-Kühne, A.; Opelz, Gerhard (Clinical & experimental immunology, 1999)
The predominant immunological finding in HIV+ haemophilia patients is a decrease of CD4+ lymphocytes during progression of the disease. Depletion of CD4+ lymphocytes is paralleled by an increase in the proportion of immune complex-coated CD4+ cells. We examined the hypothesis that the formation of immune complexes on CD4+ lymphocytes is followed by rapid clearance of immune complex-coated CD4+ lymphocytes from the circulation. In this study, the relationship of relative to absolute numbers of immune complex-loaded CD4+ blood lymphocytes and their association with viral load were studied. Two measurements of relative and absolute numbers of gp120-, IgG- and/or IgM-loaded CD4+ lymphocytes were analysed in HIV+ and HIV- haemophilia patients, with a median interval of approx. 3 years. Immune complexes on CD4+ lymphocytes were determined using double-fluorescence flow cytometry and whole blood samples. Viral load was assessed using NASBA and Nuclisens kits. Whereas the proportion of immune complex-coated CD4+ lymphocytes increased with progression of the disease, absolute numbers of immune complex-coated CD4+ lymphocytes in the blood were consistently low. Relative increases of immune complex-coated CD4+ blood lymphocytes were significantly associated with decreases of absolute numbers of circulating CD4+ lymphocytes. The gp120 load on CD4+ blood lymphocytes increased in parallel with the viral load in the blood. These results indicate that immune complex-coated CD4+ lymphocytes are rapidly cleared from the circulation, suggesting that CD4+ reactive autoantibodies and immune complexes are relevant factors in the pathogenesis of AIDS. Relative increases of immune complex-positive cells seem to be a consequence of both an increasing retroviral activity as well as a stronger loading with immune complexes of the reduced number of CD4+ cells remaining during the process of CD4 depletion. The two mechanisms seem to enhance each other and contribute to the progressive CD4 decrease during the course of the disease.
Im Titel + hochgestellt
Gesehen am 19.02.2021